A methodology for developing service in virtual manufacturing environment. (2015) - Chen, David
Abstract: Developing product related services in the context of virtual manufacturing environment to support manufacturing industry is considered as one of the main challenges for industrialised countries to improve their competiveness in the years to come. This is a complex servitization process that needs supports of appropriate models, methods and tools. This paper presents a methodological approach for the creation of the manufacturing service and service system along the engineering phases of a service life cycle. The proposed approach is developed under the frame of a FP7 European Integrated Project MSEE (Manufacturing Service Ecosystem). The methodology relates and federates a set of models, methods and tools through a structured approach. The experimentations of the methodology in industrial pilots showed that it allows the gain of time and consistency in a complex manufacturing servitization project.